The effectiveness of acceptance and commitment education on improving the mental health and quality of life of elderly people with cancer - Zohreh Hashemi; Ali Afshari; Sanaz Einy (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: Aging is a critical period of life and attention to the issues and needs of this stage is a social necessity. In recent years, aging has become one of the most important public health issues. Therefore, the main purpose of the present study was to determine the effectiveness of Acceptance and Commitment Therapy on improving quality of life in elderly with cancer. Materials and Methods: The present study was a quasi-experimental study with pretest-posttest design. In this study, 30 people were selected by convenience sampling. Quality of life questionnaire and mental health questionnaire were used for data collection. After pre-test, the study sample received 8 training sessions. Analysis of the results of covariance analysis was performed in spss23 software. Results: The results showed that treatment of admission and commitment in elderly people significantly increased in comparison with the control group, quality of life and its dimensions (physical, psychological, environmental and social dimensions) (p <0.05). The treatment also significantly increased mental health in the elderly (p <0/05). Conclusion: The results showed that acceptance and commitment training led to an increase in quality of life. Therefore, given the increasing population of elderly in developing societies including Iran and the need to pay attention to the physical and psychological health of this population, this training can be used to improve the quality of life of the elderly.